Cutting insert and method for manufacturing same
By applying a DLC hard material layer and a polysilazane cover layer on the metal substrate, the problems of poor maintenance performance and difficulty in cleaning of household cutting tool edges in the prior art are solved, and efficient and economical cutting insert manufacturing is achieved.
Patent Information
- Application Number
- CN202380066273.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-16
- Filing Date
- 2023-08-17
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to manufacture cutting inserts that can significantly improve blade retention and easy cleaning in household cutting tools in a cost-effective manner, and the manufacturing process of multi-layer systems is complex and time-consuming.
By applying a DLC hard material layer on the metal substrate and applying a cover layer by wet treatment on the side of the DLC hard material layer away from the substrate, ensuring that there is no direct cover layer or the thickness of the cover layer is reduced at the cutting edge, polysilazane is used as the cover layer material.
Good initial sharpness of the cutting insert and durable cutting edge retention characteristics are achieved, while making the insert easy to clean with standard household products and reducing manufacturing costs.
Smart Images

Figure CN119895073A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cutting insert and a method for producing the same. The cutting insert comprises a metal substrate having a first cutting surface and a second cutting surface, the first cutting surface and the second cutting surface comprising a cutting edge, wherein at least one DLC hard material layer is applied to the substrate, and at least one covering layer is applied to the DLC hard material layer via a wet process on the side facing away from the substrate, and one covering layer directly at the cutting edge has no covering layer or has a covering layer with a reduced layer thickness compared to the remaining covering layer. In addition, the invention relates to a method for producing such a cutting insert. Background Art
[0002] According to the prior art, there are numerous inventions which aim to optimize the cutting performance of knives, cutters, scissors or similar tools using coatings. However, according to DIN EN 10020 (July 2000), the following intellectual property rights do not apply or only apply to a limited extent to household cutting knives made of conventional rust-proof stainless steel.
[0003] For example, EP2495081B1 describes a cutting tool with a fine-grained diamond coating. It is applied in a hot-wire CVD process at typical substrate temperatures between 600°C and 900°C. The substrate is made of a temperature-resistant material such as titanium, nickel, niobium, tungsten, carbide or ceramic. These temperatures are much higher than the tempering temperature of stainless steel. Changing the material to one of those mentioned would also lead to a significant increase in the cost of a household knife.
[0004] US 6,289,593 B1 describes a razor blade with a DLC layer having an edge radius of less than 1200 angstroms (equivalent to 0.12 μm) and a layer thickness of at least 400 to 2000 angstroms (equivalent to 0.04 μm to 0.2 μm). However, such a small edge radius and a small layer thickness are not sufficient to significantly increase the edge holding properties of household knives. This is because the operating conditions and handling of household knives are rougher than those of razor blades.
[0005] DE 102019200681 A1 describes a multilayer cutting tool in which an intermediate layer consists of hybridized carbon, forming the cutting edge. Since the thickness of these layers is in the micrometer range, it is not possible to produce these layers in a cost-effective manner from the point of view of manufacturing technology. This would require grinding the cutting edge with micrometer accuracy, which is very time-consuming. When applying thicker layers using thermal spraying, there is the disadvantage that the corrosion resistance of the typical stainless steel blade material is reduced. In addition, it is not economically feasible to produce such a multilayer structure for consumer products, and especially for knives with complex geometries.
[0006] EP 3683332 A1 also describes a hybrid carbon coating on a carrier substrate which, compared to DE 10 2019 200 681 A1, has a three-dimensional structure. This structuring can be achieved by masking, but this is very time-consuming. The subsequent laser treatment has the disadvantage that the heat energy input will lead to a reduction in the corrosion resistance of the stainless steel substrate.
[0007] DE 102004052068 B4 describes a cutting tool with a metal support layer and a second layer of diamond-like carbon. In this case, only the maximum edge rounding is defined, but not the layer thickness. Both parameters are necessary for good initial sharpness and for maintaining cutting performance during the longest possible service life.
[0008] EP 2714964 B1 details a woodworking knife with defined layer thickness and cutting edge rounding. However, if the sliding layer mentioned in claim 1, which is necessary for a cost-effective solution, is omitted, this will result in different layer thicknesses and different edge roundings. The object of the present invention is to avoid a cost-intensive multilayer system consisting of a sliding layer and a functional layer, which is applied in a two-step process. Furthermore, the patent describes substrates made of carbide, HSS, ceramic or cermet, which are not suitable materials for household knives.
[0009] Another problem associated with the coating of consumer products is the increase in roughness caused by the application of the DLC layer. This effect increases with increasing layer thickness. This is caused by defects in the layer growth (so-called droplets). One solution is to use a different coating method, such as HiPIMS or high-power impulse magnetron sputtering, as described in DE 102008021912C5 or EP2017366 B1. However, this will be expensive and only reduces the problem.
[0010] Typically, carbon layers are not easy to clean after becoming contaminated. This problem is exacerbated by the increased roughness to the point where adequate cleaning with standard household products is no longer possible.
[0011] DE 102015101782 B4 describes a sliding layer applied to a DLC layer. In this case, the DLC or PLC layer described does not lead to a reduction in roughness or does not eliminate the increased roughness of the DLC base layer. In addition, the affinity of food for carbon-based coatings makes them difficult to clean. In addition, another PVD or CVD process would lead to high costs and could result in increased cutting edge rounding, resulting in reduced sharpness.
[0012] EP 1915472 B1 also describes a multilayer structure consisting of a hard tetrahedral carbon middle layer and a softer amorphous carbon cover layer. With regard to the application of these layers and the coating material itself, the disadvantages are consistent with the above patent description. Summary of the invention
[0013] Based on this, the object of the present invention is to eliminate the disadvantages existing in the prior art and to provide a cutting insert which is sharp when delivered and which retains its sharpness and cutting performance for as long as possible even under increased load. Furthermore, the cutting insert should be easy to clean with standard household products. Furthermore, the cutting insert should be manufactured using a cost-effective method.
[0014] This object is achieved by a method for producing a cutting insert having the features of claim 1 and a cutting insert having the features of claim 9. Further dependent claims describe preferred embodiments.
[0015] According to the present invention, a method for manufacturing a cutting insert is provided, wherein
[0016] a) a DLC hard material layer is applied via physical vapor deposition (PVD) to a substrate having a first cutting surface including a cutting edge and a second cutting surface,
[0017] b) applying a coating solution onto the DLC hard material layer using a dipping and / or spraying process, the coating solution having a strength of 18 to 40 mJ / m 2 The surface tension of
[0018] c) While the coating solution is drying and forming a covering layer, the coating solution withdraws from the cutting edge due to its surface tension, so that there is no direct covering layer at the cutting edge or a covering layer with a smaller layer thickness than the remaining covering layer.
[0019] Preferably, at least one DLC hard material layer contains amorphous carbon, in particular tetrahedral amorphous carbon, or consists of it. The advantage of tetrahedral amorphous carbon layers is their outstanding hardness and therefore their wear resistance. In addition, other hard material layers can also be used, which can be applied by PVD, PECVD, CVD or thermal spraying processes.
[0020] Compared to solutions known from the prior art, the cutting insert according to the present invention benefits from the ability to ensure good initial sharpness and long-lasting cutting edge retention properties.
[0021] In a preferred embodiment, at least one DLC hard material layer is applied to the substrate with a thickness in the range of 1 to 5 μm, particularly preferably 2 to 4 μm, more preferably 2.5 to 3.5 μm.
[0022] In a further preferred embodiment, it is provided that in step c) a covering layer is formed directly on the cutting edge, said covering layer having a layer thickness which is 3 times smaller, preferably 5 times smaller, particularly preferably 10 times smaller than the rest of the covering layer.
[0023] At least one cover layer with a thickness in the range of 0.2 to 3 μm, preferably 0.5 to 2.5 μm, particularly preferably 1 to 2 μm, is applied to the DLC hard material layer. It must be ensured that the layer thickness remains within a defined process window. A certain layer thickness is required in order to even out any micro-roughness. Furthermore, for reasons of cost and layer adhesion, a certain layer thickness should not be exceeded.
[0024] The coating solution preferably has a concentration of 20 to 30 mJ / m 2 , particularly preferably 22 to 26 mJ / m 2 The surface tension is within the range of .
[0025] The application of the coating or the complete coating process should preferably be carried out at a temperature below 250° C., preferably below 220° C., particularly preferably below 200° C.
[0026] Preferably, the coating solution contains or consists of polysilazane. No costly vacuum process is required. After appropriate pre-cleaning, this can be applied by spraying with a solvent or immersion in a solvent. No costly vacuum process is required. In addition, the polysilazane layer remains stable in a pH range of 3 to 12.
[0027] In addition to polysilazane layers, glass or glass-like layers or hybrid layers, ceramic-based layers or other anti-fingerprint coatings, and polymer resin or fluoropolymer layers may also be used.
[0028] Preferably, the metal substrate material is selected from the group consisting of steel, ceramic, carbide and combinations thereof, in particular stainless steel. Stainless steel with a minimum of 10.5% chromium and a maximum of 1.2% carbon is a preferred substrate, preferably with more than 12% chromium and less than 0.8% carbon, particularly preferably with more than 14% chromium and 0.4-0.6% carbon. Particularly preferred are stainless steels with steel keys 1.4116, 1.4125, 1.4031, 1.4028, 1.4021, 1.4034, 1.4122 or 1.4006. Other suitable steel keys can be found here: www.edelstahl-rostfrei.de / fileadmin / user_upload / ISER / images
[0029] / publikationen / Dok_Martensite_final.pdf.
[0030] The cutting insert comprises a metal substrate having a first cutting surface and a second cutting surface, the first cutting surface and the second cutting surface comprising a cutting edge, wherein at least one DLC hard material layer is applied on the substrate, and at least one covering layer applied via a wet process is deposited on the side of the DLC hard material layer facing away from the substrate, and one covering layer directly at the cutting edge has no covering layer or has a covering layer with a reduced layer thickness compared to the remaining covering layers.
[0031] Preferably, at least one DLC hard material layer contains amorphous carbon, in particular tetrahedral amorphous carbon, or consists thereof. Due to its outstanding hardness and thus its wear resistance, tetrahedral amorphous carbon layers are particularly suitable.
[0032] A preferred embodiment provides that the at least one DLC hard material layer preferably has a hardness of at least 30 GPa, particularly preferably at least 34 GPa, very particularly preferably 38 GPa to 45 GPa.
[0033] The at least one DLC hard material layer preferably has a thickness in the range of 1 to 5 μm, preferably 2 to 4 μm, particularly preferably 2.5 to 3.5 μm.
[0034] The cover layer preferably comprises or consists of polysilazane, since polysilazane is stable in the pH range of 3 to 12. Polysilazane cover layers are highly resistant to chemicals and mechanical abrasion. Covalent bonds to the substrate or underlying DLC layer help achieve this.
[0035] The cover layer should adhere well to the substrate and the underlying DLC layer. The cover layer preferably has a cross-sectional value determined in accordance with DIN EN ISO 2409 of 0 to 2, particularly preferably 0 to 1, particularly preferably 0.
[0036] In addition to polysilazane layers, glass or glass-like layers or hybrid layers, ceramic-based layers or other anti-fingerprint coatings, and polymer resin or fluoropolymer layers may also be used.
[0037] Preferably, the coating thickness of the covering layer is reduced by a factor of 3, preferably by a factor of 5, particularly preferably by a factor of 10 directly at the cutting edge compared to the rest of the covering layer.
[0038] Furthermore, the covering layer preferably has a thickness in the range of 0.2 to 3 μm, preferably 0.5 to 2.5 μm, particularly preferably 1 to 2 μm.
[0039] The cover layer preferably has a surface roughness Ra of 0.05 to 0.22 μm, particularly preferably 0.08 to 0.20 μm.
[0040] The cover layer preferably has a strength of 10 to 30 mJ / m 2, particularly preferably 15 to 25 mJ / m 2 This ensures that if they become dirty they can be easily cleaned.
[0041] Preferably, the metal substrate material is selected from the group consisting of steel, ceramic, carbide and combinations thereof, in particular stainless steel. Stainless steel with a minimum of 10.5% chromium and a maximum of 1.2% carbon is a preferred substrate, preferably with more than 12% chromium and less than 0.8% carbon, particularly preferably with more than 14% chromium and 0.4-0.6% carbon. Stainless steel with steel key 1.4116 is particularly preferred.
[0042] Preferably, the angle between the first cutting surface and the second cutting surface is in the range of 15° to 40°, preferably in the range of 20° to 35°, and particularly preferably in the range of 25° to 32°.
[0043] In order to achieve good initial sharpness, the rounding radius of the cutting edge is preferably in the range from 1 to 6 μm, particularly preferably 1.5 to 5 μm and most particularly preferably 2 to 4 μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] The following figures and examples are intended to explain the subject matter of the invention in more detail without intending to limit it to the specific embodiments shown herein.
[0045] In the attached figure:
[0046] Figure 1 is a cross-sectional view of a cutting insert according to the present invention;
[0047] Figure 2 is a first microscopic image of a cutting edge of a cutting insert according to the present invention;
[0048] Figure 3 Yes Figure 2 Another microscopic image of higher resolution of the cutting edge of the cutting insert according to the invention is shown;
[0049] Figure 4 Another microscopic image of a cutting insert according to the invention, detailing the structure of the coating;
[0050] Figure 5 is a graph showing the cutting performance of a cutting insert according to the present invention compared to an uncoated cutting insert of the prior art. DETAILED DESCRIPTION
[0051] The cutting insert 1 of the present invention is as follows Figure 1The cutting insert 1 consists of a substrate 2, the first cutting surface 3 and the second cutting surface 4 of which are coated with a DLC hard material layer 6. The DLC hard material layer in turn has a covering layer 7 made of polysilazane. Figure 1 The figure in shows that the thickness of the cover layer 7 at the cutting edge 5 decreases towards the cutting edge 5: this is due to edge loss.
[0052] Figure 2 A microscopic image of a cutting insert 1 according to the invention is shown in the region of a cutting edge 5. The cutting edge 5 is surrounded by a first cutting surface 3 (top) and a second cutting surface 4 (bottom).
[0053] and Figure 2 similar, Figure 3 The cutting insert 1 according to the invention is shown in the region of the cutting edge 5 , but at a higher resolution.
[0054] Figure 4 A microscopic image of a cutting insert 1 according to the invention is shown in cross section, which shows the structure of the coating. Here a DLC hard material layer 6 is applied to a substrate 2. The DLC hard material layer has a layer thickness of 2.58 μm. The DLC hard material layer 6 is coated with a covering layer of polysilazane 7, wherein an interface 8 between the two coatings can be seen. The covering layer has a layer thickness of 1.51 μm. Figure 4 It is shown that in areas 9 , 10 , due to uneven coating, the DLC hard material layer 6 has a higher or smaller layer thickness, and the cover layer 7 can compensate for these deviations and show a smoothing effect, so that the surface of the cover layer 7 has a very low surface roughness, making the surface very easy to clean.
[0055] Figure 5 The graph in shows the cutting performance of a cutting insert according to the present invention compared to an uncoated steel insert. For the uncoated steel insert according to the prior art, it can be easily appreciated that the cutting depth decreases rapidly after only a few cutting cycles, whereas the cutting depth of the cutting insert according to the present invention remains substantially constant even after 60 cutting cycles.
[0056] Examples
[0057] First, the blade body is made of a selected material. Due to manufacturing tolerances, this can be done by cutting the steel (by laser, stamping, etc.) to produce a steel band knife or by forging the blade from a solid steel sheet. Martensitic corrosion-resistant steels, such as 1.4116 or X50CrMoV15, which offer a good combination of hardness and corrosion resistance, are preferred blade materials. In principle, other steel alloys are also suitable.
[0058] The next step in the process is tempering the blade. In this method, the blade is hardened during the hardening process and then tempered one or more times. The purpose of this two-step method is to improve wear resistance and subsequently optimize toughness. This method is widespread in industry. In order to obtain a uniform and fine grain size, a normalizing heat treatment can be carried out beforehand in some cases.
[0059] The hardened blade body is then ground or polished in a process that typically includes several steps. This achieves the final profile in terms of dimensional accuracy, creates an attractive appearance, and improves corrosion resistance.
[0060] One of the last steps is to attach or grind the cutting edge. The cutting edge angle is typically in the range of 15° to 40°, preferably from 20° to 35°, particularly preferably from 25° to 32°. The rounded cutting edge is also crucial for the initial sharpness. The rounding radius should be less than 6 μm, preferably less than 5 μm, particularly preferably less than 4 μm.
[0061] The DLC layer is then applied. Pre-cleaning (wet chemistry, ultrasound, etc.) is usually required, as well as plasma fine cleaning in a PVD system to activate the surface before applying the actual DLC layer in the same system. A tetrahedral amorphous layer with excellent wear resistance is preferred here. The hardness of this layer should be at least 30 GPa, preferably at least 34 GPa, particularly preferably at least 38 GPa. In order to improve adhesion, an adhesion promoting layer consisting of or containing chromium or titanium may be required.
[0062] The layer thickness should be in the order of 1 to 5 μm, preferably 2 to 4 μm, particularly preferably 2.5 to 3.5 μm. It is also very important that the layer adheres well to the substrate and the cutting edge. The layer adhesion, tested according to DIN 4856, should be between HF1 and HF3, preferably between HF1 and HF2, particularly preferably HF1.
[0063] The final coating step is the application of a cover layer, which is preferably a polysilazane layer. In addition to the polysilazane layer, glass or glass-like layers or hybrid layers, ceramic-based layers or other anti-fingerprint coatings, and polymer resins or fluoropolymer layers may also be used. Applying the coating ensures a reduction in roughness and also makes the blade easier to clean with standard household products.
[0064] Before applying the layer, the knife is usually cleaned. The polysilazane layer can be applied by dipping or spraying and then dried or baked in an oven. The dried coating has a surface tension of 20 to 30 mJ / m 2 , preferably 22 to 26 mJ / m 2The cover layer should have a cross-sectional value of 0 to 2, particularly preferably 0 to 1, particularly preferably 0, determined according to DIN EN ISO 2409.
[0065] The effect of edge loss during drying means that the thickness of the cover layer is lower during drying than the rest of the cover layer. The reduction in layer thickness from the side surface to the cutting edge is of the order of magnitude of 3, preferably 5, particularly preferably 10 times. This minimizes the rounding of the cutting edge to a minimum and thus avoids measurable losses in sharpness.
[0066] Attach the handle if not already done in the previous step.
Claims
1. A method for manufacturing a cutting insert (1), wherein a) a DLC hard material layer (6) is applied via physical vapor deposition (PVD) onto a substrate (2), said substrate (2) having a first cutting surface (3) including a cutting edge (5) and a second cutting surface (4), b) applying a coating solution onto the DLC hard material layer (6) by dipping and / or spraying, wherein the coating solution has a viscosity of 18 to 40 mJ / m 2 The surface tension, and c) while drying the coating solution, a covering layer (7) is formed, the coating solution withdraws from the cutting edge (5) due to its surface tension, so that there is no direct covering layer (7) at the cutting edge (5) or a covering layer (7) with a smaller layer thickness than the remaining covering layer (7).
2. The method according to claim 1, It is characterized in that The at least one DLC hard material layer (6) contains or consists of amorphous carbon, in particular contains or consists of tetrahedral amorphous carbon.
3. The method according to any one of claims 1 or 2, It is characterized in that The at least one DLC hard material layer (6) is applied to the substrate (2) with a thickness in the range of 1 to 5 μm, preferably 2 to 4 μm, particularly preferably 2.5 to 3.5 μm.
4. The method according to any one of claims 1 to 3, It is characterized in that In step c), a covering layer (7) is formed directly on the cutting edge (5), said covering layer having a layer thickness which is 3 times smaller, preferably 5 times smaller, particularly preferably 10 times smaller than the rest of the covering layer (7).
5. The method according to any one of claims 1 to 4, It is characterized in that At least one covering layer (7) having a thickness in the range of 0.2 to 3 μm, preferably 0.5 to 2.5 μm, particularly preferably 1 to 2 μm, is applied to the DLC hard material layer (6).
6. The method according to any one of claims 1 to 5, It is characterized in that The coating solution has a strength of 20 to 30 mJ / m 2 , particularly preferably 22 to 26 mJ / m 2 The surface tension is within the range of .
7. The method according to any one of claims 1 to 6, It is characterized in that The coating solution contains polysilazane.
8. The method according to any one of claims 1 to 7, It is characterized in that The material of the metal substrate is selected from the group consisting of steel, ceramic, carbide and combinations thereof, in particular stainless steel, preferably stainless steel with steel keys 1.4116, 1.4125, 1.4031, 1.4028, 1.4021, 1.4034, 1.4122 or 1.4006.
9. The cutting insert (1) comprises a metal substrate (2) having a first cutting surface (3) and a second cutting surface (4), wherein the first cutting surface and the second cutting surface comprise a cutting edge (5), and at least one DLC hard material layer (6) is applied to the substrate (2), and at least one covering layer (7) is applied via a wet process on the side of the DLC hard material layer (6) facing away from the substrate (2), and the one covering layer (7) directly at the cutting edge (5) has no covering layer (7) or has a covering layer (7) with a reduced layer thickness compared to the remaining covering layers (7).
10. The cutting insert according to claim 9, It is characterized in that The at least one DLC hard material layer (6) contains or consists of amorphous carbon, in particular contains or consists of tetrahedral amorphous carbon.
11. The cutting insert according to claim 9 or 10, It is characterized in that The at least one DLC hard material layer (6) has a hardness of at least 30 GPa, preferably at least 34 GPa, more preferably 38 GPa to 45 GPa.
12. The cutting insert according to any one of claims 9 to 11, It is characterized in that The at least one DLC hard material layer (6) preferably has a thickness in the range of 1 to 5 μm, preferably 2 to 4 μm, particularly preferably 2.5 to 3.5 μm.
13. The cutting insert according to any one of claims 9 to 12, It is characterized in that The cover layer contains polysilazane or consists of polysilazane.
14. The cutting insert according to any one of claims 9 to 13, It is characterized in that The coating thickness of the covering layer (7) directly at the cutting edge (5) is 3 times smaller, preferably 5 times smaller, particularly preferably 10 times smaller than the rest of the covering layer (7).
15. The cutting insert according to any one of claims 9 to 14, It is characterized in that The thickness of the cover layer (7) is in the range of 0.2 to 3 μm, preferably 0.5 to 2.5 μm, particularly preferably 1 to 2 μm.
16. The cutting insert according to any one of claims 9 to 15, It is characterized in that The cover layer has a surface roughness Ra of 0.05 to 0.22 μm, preferably 0.08 to 0.20 μm.
17. The cutting insert according to any one of claims 9 to 16, It is characterized in that The material of the metal substrate is selected from the group consisting of steel, ceramic, carbide and combinations thereof, in particular stainless steel, preferably stainless steel with steel key 1.4116.
18. The cutting insert according to any one of claims 9 to 17, It is characterized in that The angle between the first cutting surface (3) and the second cutting surface (4) is in the range of 15° to 40°, preferably 20° to 35°, and particularly preferably 25° to 32°.
19. The cutting insert according to any one of claims 9 to 18, It is characterized in that The cutting edge (5) has a rounding radius of 1 to 6 μm, preferably 1.5 to 5 μm, particularly preferably 2 to 4 μm.
20. A cutting insert according to any one of claims 9 to 19 and producible by a method according to any one of claims 1 to 8.
Citation Information
Patent Citations
cutting tool and its use
DE102004052068B4
coating process
DE102008021912C5
sliding element
DE102015101782B4
Cutting tool with amorphous carbon and multilayer coating and method for its manufacture
DE102019200681A1
Substrate coated with a layered structure comprising a tetrahedral carbon layer and a softer outer layer
EP1915472B1